Genetic mutations in non-syndromic deafness patients in Hainan Province have a different mutational spectrum compared to patients from Mainland China. (May 2018) - Huang, Bangqing; Han, Mingyu; Wang, Guojian; Huang, ShaSha; Zeng, Jialing; Yuan, Yongyi; Dai, Pu
Abstract: Objectives: To provide appropriate genetic testing and counseling for non-syndromic hearing impairment patients in Hainan Province, an island in the South China Sea. Methods: 299 unrelated students with non-syndromic hearing loss who attended a special education school in Hainan Province were enrolled in this study. Three prominent deafness-related genes ( GJB2, SLC26A4, and mtDNA 12S rRNA ) were analyzed using Sanger sequencing. Results: GJB2 mutations were detected in 32.78% (98/299) of the entire cohort; however, only 5.69% (17/299) had two confirmed pathogenic mutations. The most common mutation observed in this population was c.109G > A in the GJB2 gene, with an allelic frequency of 15.05% (90/598), which is significantly higher than that reported in previous cohorts. A total of 16 patients had two confirmed pathogenic SLC26A4 gene mutations, and 16 patients had one. The IVS7-2A > G mutation was the most commonly observed, with an allelic frequency of 3.51% (21/598). Three patients had a m.1555A > G mutation in the mtDNA 12S rRNA gene. Conclusions: These results reveal that genetic etiology occurred in 11.71% (35/299) of patients, suggesting that Hainan province have a different mutational spectrum compare to Mainland China in non-syndromic deafness patients, which provide useful information to genetic counseling in Hainan province.